STRATEGI BADAN PENGAWAS PEMILIHAN UMUM (BAWASLU) KOTA SURABAYA DALAM UPAYA MENCEGAH PELANGGARAN PEMILIHAN UMUM 2024 MELALUI MEDIA SOSIAL - Mahmudah, Amanah Amalia; Tukiman, Tukiman (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
In the 2024 general elections, the role of social media is very significant. The General Election Supervisory Agency (Bawaslu) as an institution tasked with overseeing the implementation of elections, has a big responsibility in providing education to the public to prevent violations that could occur. This study aims to explore and understand the strategies implemented by Bawaslu Surabaya City in preventing election violations. The method used in this research is qualitative with a filed research approach. Data processing and presentation are carried out through qualitative analysis techniques, which include interpretation, description, management, and interpretation of research results as a representation of the characteristics or description of certain phenomena related to the problem under study. Data collection is done through observation, interviews, and document studies. In this research, the author refers to the theory of democratic elections and supervision theory. The results showed that the Surabaya City Bawaslu utilized social media as a tool to support supervision in an effort to prevent election violations. However, the implementation is still not optimal because there are still obstacles that need to be reviewed.